Hubungan Antara Tingkat Pendidikan dan Tingkat Pengetahuan Masyarakat Terhadap Kejadian Demam Berdarah - Yandika, Ananda Putri (Publikasi Indonesia, 2022)
Dengue hemorrhagic fever (DHF) is a health problem in Indonesia that tends to show an increase in the number of sufferers and distribution areas. There are various obstacles to reducing the number of DHF sufferers, including the lack of public knowledge about dengue transmission and knowledge to prevent dengue infection. Based on the Health Office of Kalideres Sub-district, West Jakarta, there were 480 cases of dengue fever during January-December 2015; in Kalideres Sub-district, West Jakarta, there were 60 patients. This study aims to determine the level of education and knowledge of the community regarding dengue prevention behavior in Kalideres District, West Jakarta. The research was conducted on the community in Kalideres Sub-district, West Jakarta in October-November 2016 using a cross-sectional study design. The sampling was 100 respondents using a random sampling technique. The instrument used was a questionnaire with data analysis using the Chi-square test. Based on 100 samples, 55.0% of respondents had good knowledge and respondents with poor knowledge 35.0%, respondents with high education 78.0% and respondents with low education 22.0%, respondents who took good precautions 63.0% and respondents who took less prevention 37.0%. The results of the bivariate analysis showed a significant relationship between the variable level of education and preventive behavior (p=0.008), and there was a significant relationship between the variable level of knowledge and preventive behavior. Through counseling as an effort to provide knowledge for the community, it is hoped that public awareness and a better understanding of dengue fever can be achieved.